Of cockroaches and crickets : learning to love creatures that skitter and jump - Nischk, Frank (Greystone Books, 2023)
"For many people, cockroaches are the most pesky of pests. Not so for entomologist Frank Nischk. In this funny and fascinating book, Frank reveals his love and admiration for so-called "nasty" creatures like cockroaches, crickets, and more. He shows us that even seemingly terrifying insects are beautiful in their own way--and essential to all life on Earth." -- from Amazon.